Profile of Patients with Floaters in Saiful Anwar Hospital Malang - Hidayah, Fenti Kusumawardhani; Dewi, Nadia Artha; Refa, Safaruddin (International Journal of Retina, 2018)
Introduction: To report the profile of patients with floaters as a subjective complain in Saiful Anwar Hospital from July 2012 until June 2013. Methods: an observasional descriptive study was conducted, collecting data on gender, age, subjective complain (floaters, flashes and subjective vision reduction), best corrected visual acuity and diagnose from patientâs medical record. Result: 169 patients (215 eyes) were included in this study. Female patients contributed a higher percentage than male with mean of age was 49 years old. The subjective complain was floaters (67%), floater with blurred vision (22%), floater with flashes (6%) and patients with floaters, flashes, and blurred vision was 5%. Myopia was the most common refraction problem. Diagnose recorded from this study were posterior vitreous detachment (PVD) (34%), no abnormalities (13%), PDR (10%), RRD (9%), peripheral retinal degeneration (14%) retinal break (6%), corpus vitreous degeneration (3%), vitreous haemorhage (3%), posterior uveitis (2%) and others (6%). Conclusion: The most common cause of floaters is PVD. Even it is usually a save condition but there are some condition with floater as a subjective complain which is threatening vision, so accurate eye examination from anterior to posterior segment were needed.